PENGEMBANGAN E-MODUL KIMIA PANGAN 3 BERBASIS KONSTRUKTIVISME LIMA FASE NEEDHAM PADA PROGRAM STUDI PENDIDIKAN KIMIA - Kintan Afifah Salsabila; A. Rachman Ibrahim; Andi Suharman (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2022)
This research is a development research that aims to produce a product in the form of e-module Food Chemistry 3 Based on Needham Five Phase Constructivism at the Chemistry Education Study Program, Sriwijaya University with food processing, food braising and food packaging. The researcher uses a 4D development model (Define, Design, Develop, Disseminate) modified by Tessmer. The results of the e-module validity test on the pedagogic, design and material aspects according to V Aiken are included in the valid category with each aspect sequentially, namely 0.97, 0.97 0.97. Practicality test on e-module development stage testing belongs to the very practical category with reliable values at the development testing stage 1 and development testing 2, respectively, namely 0.900 and 0.711. The effectiveness test on the e-module in the field test stage is classified as effective with an n-gain score of 0,91. Based on the results of the evaluation, it shows that the e-module developed is included in the valid, practical and effective criteria.